New Discoveries in Enantiomeric Separation of Racemic Tofisopam - Miklós Hunor Bosits; Emese Pálovics; János Madarász; Elemér Fogassy (Journal of Chemistry)
Resolution process of tofisopam has been re-evaluated now based on our new investigations. Originally, it was carried out in the water-chloroform system, where the intermediate salt of high diastereomeric excess was described as (R)-TOF·(R,R)-DBTA·(H2O)3. Opposed to previous assumptions, we have actually found that a different solvate composition, (R)-TOF‐(R,R)-DBTA-CHCl3, forms with chloroform, in which molecules of CHCl3 are captured and held with different strengths. Moreover, resolution of TOF with (R,R)-DBTA is possible (and favourable) in water-free solvent and solvent mixture. However, presence of chloroform is essential, and thus, chloroform is also a suitable solvent alone. Among the tested solvents, toluene-chloroform mixture results in the highest resolution efficiency, while the highest enantiomeric purity was achieved when acetonitrile was in the system too. Resolution efficiency can be also increased by using the quasi-racemic resolving agent and thermodynamic control. Purification of enantiomeric mixtures was examined, and recrystallization of the diastereomeric salt was found to be the most efficient solution. Instructive behaviour of the complex enantiomer-conformer system of tofisopam is emphasized.